Blast densification: A proposed methodology to quantify the amount of densification required to prevent liquefaction and flow in sandy soils - Carlos Alberto Vega-Posada; David Guillermo Zapata-Medina; Alfonso Mariano Ramos-Cañon (Revista Facultad de Ingeniería Universidad de Antioquia, 2016)
This paper presents a methodology to quantify the amount of blast densification or number of passes required for a given project to prevent liquefaction and flow in saturated, loose sandy soils. The proposed methodology is based on the concepts of the critical state soil mechanics, and the number of passes is chosen so that the final state of stresses of the blasted layer is located below the critical state line of the soil, where a dilative response is expected. Field and laboratory results of a blast densification program conducted at a waste disposal landfill located in South Carolina, USA, are presented and used to evaluate the proposed approach. A step-by-step example is presented in detail for this purpose. This methodology could provide to engineers a rational manner to estimate how much improvement is required in the soil to meet the design objective of a particular project and the costs associated with it.